When the ureter slips: A rare case of ectopic uretero-inguinal hernia and its clinical implications - Vikram Prabha; Sanhitha Purushotham (Urology Case Reports)
Congenital anomalies like duplex renal collecting systems and ectopic ureters are rare. We report a unique case of a 61-year-old male presenting with left inguinal swelling, recurrent epididymo-orchitis, and LUTS. CT revealed a duplex collecting system with an ectopic ureter containing multiple calculi, terminating in the left inguinal region. The patient underwent laparoscopic ectopic ureterectomy and inguinal hernia repair. This case highlights the rare presentation of a uretero-inguinal hernia with an ectopic ureter containing multiple calculi inserting into the epididymis as its content. Laparoscopic management proved effective in treating this complex congenital urinary tract anomaly.